Narrative analysis of media coverage of Philippines's tourism policies during the Covid-19 pandemic (2020-2021) - Dicky Izmi Syahputra; Dyah Mutiarin (Universitas Muhammadiyah Yogyakarta, 2022)
The primary objectives of the study are to investigate the manner in which the media in the Philippines covered the Covid-19 outbreak and to investigate the effects that the outbreak had on the public policy of the country with regard to the tourism industry. For the purpose of this study, examples were drawn from various news articles published on CNN Philippines, Inquirer.net, and pna.gov.ph that covered the years 2020 and 2021. The analysis makes use of the Nvivo software to produce a Word Cloud, which is a list of the terms and keywords that occurred the most frequently over the specified time period. Additionally, the percentage of variable analysis, also known as the percentage of media reporting narratives against predetermined variables, was also calculated. The variables that were used in this study were UNWTO recommendations that were compiled in relation to the tourism sector as a response to the impacts caused by the Covid-19 pandemic. The media has assumed a prominent position during the epidemic as a result of the value and utility it serves in today's modern society. The role of the media in society is also on display during the pandemic, as evidenced by the media's constant dissemination of pandemic-related information and the creation of hospitable conditions in the community at large, particularly in the tourism sector, where it plays an active role in disseminating crucial information to the various actors in Indonesia's tourism industry. The media's role in society is also on display during the pandemic, as evidenced by the media's constant dissemination of pandemic-related.